PENGARUH PENDEKATAN REALISTIC MATHEMATIC EDUCATION PADA MATERI OPERASI BENTUK ALJABAR DI SMP - Nasyrullah, Much; Halini, Halini; Yani T, Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is aimed to know the influence of the Realistic Mathematic Education approach on student learning outcomes in algebraic operating material in VII the grade of SMP Pancasila Sungai Kakap. The method is used in this research is an experimental the one shot case study. For looked at the consistency of learning outcomes, so after two week later would be given delayed-test. From the result of the research obtained the average student learning outcomes on the posttest is 77.25 and the average student learning outcomes on the delayed test is 72.05. Based on the analysis result by using t test the average one sample is obtained that t count (3,89) > t table (2,09) so, there was a significant differences between the average value of students at posttest and delayed test. With the differences in the results of posttest and delayed test then there is inconsistency between the value of posttest and delayed test. It is means that the application of the Realistic Mathematic Education approach to in algebraic operating material does not influence of on students learning outcomes.Â Keywords: Influence, Realistic Mathematic Education, Learning Outcomes